Art Basel - year 47 - Dirié, Clément 1981-
Art Basel's official annual publication captures and documents the exhibitions in Basel, Miami Beach, and Hong Kong, and goes beyond them, featuring interviews, portfolios, essays about contemporary art, and personal highlights from artists, curators, collectors, and museum directors.0With its A-to-Z format, this year's publication maps the world of Art Basel alongside profiles spotlighting each of the 500+ galleries that participated across the three shows in 2016. Designed by Gavillet & Cie (Geneva), it features all the different sectors of the fair, highlights events, talks, Art Basel's new initiatives, and retrospective insights into the very first years of the fair, offering vivid and varied perspectives on the global art world as seen through the eyes of Art Basel in 2016. Giving art world experts, curators, and collectors a platform for sharing their expertise, the publication provides an insightful and immersive art experience for the reader.00Exhibition: Messe Basel,Switzerland (16.06. - 19.06.2016) / Miami Beach Convention center, Florida, USA (01.12. - 04.12.2016) / Convention and exhibition center, Hong Kong, China (24.03. - 26.03. 2016).0
Keywords: Art Basel -- 47. -- 2016 -- Basel; Geschichte 2016; Kunst; Katalog